Thermal design optimization of novel modular power converter assembly enabling higher performance, reliability and availability - Cova, P.; Delmonte, N.; Solomon, A.K.; Castellazzi, Alberto (Elsevier, 2016)
An alternative integration scheme for a half-bridge switch using 70 μm thin Si IGBTs and diodes is presented. This flat switch, which is designed for high-frequency application with high power density, exhibits high strength, high toughness, low parasitic inductance and high thermal conductivity. Such a novel assembly approach is suitable to optimize performance, reliability and availability of the power system in which it is used. The paper focuses on the thermal performance of this assembly at normal and extreme operating conditions, studied by means of FEM thermo-fluidynamic simulations of the module integrated with connectors and liquid cooler, and thermal measurement performed on an early prototype. Improved solutions are also investigated by the FE model.